Altered glycosylation of complexed native IgG molecules is associated with disease activity of systemic lupus erythematosus. (May 2015) - Sjöwall, C; Zapf, J; von Löhneysen, S; Magorivska, I; Biermann, M; Janko, C; Winkler, S; Bilyy, R; Schett, G; Herrmann, M; Muñoz, L E
In addition to the redundancy of the receptors for the Fc portion of immunoglobulins, glycans result in potential ligands for a plethora of lectin receptors found in immune effector cells. Here we analysed the exposure of glycans containing fucosyl residues and the fucosylated tri-mannose N-type core by complexed native IgG in longitudinal serum samples of well-characterized patients with systemic lupus erythematosus. Consecutive serum samples of a cohort of 15 patients with systemic lupus erythematosus during periods of increased disease activity and remission were analysed. All patients fulfilled the 1982 American College of Rheumatology classification criteria. Sera of 15 sex- and age-matched normal healthy blood donors served as controls. The levels and type of glycosylation of complexed random IgG was measured with lectin enzyme-immunosorbent assays. After specifically gathering IgG complexes from sera, biotinylated lectins Aleuria aurantia lectin and Lens culinaris agglutinin were employed to detect IgG-associated fucosyl residues and the fucosylated tri-mannose N-glycan core, respectively. In sandwich-ELISAs, IgG-associated IgM, IgA, C1q, C3c and C-reactive protein (CRP) were detected as candidates for IgG immune complex constituents. We studied associations of the glycan of complexed IgG and disease activity according to the physician's global assessment of disease activity and the systemic lupus erythematosus disease activity index 2000 documented at the moment of blood taking. Our results showed significantly higher levels of Aleuria aurantia lectin and Lens culinaris agglutinin binding sites exposed on IgG complexes of patients with systemic lupus erythematosus than on those of normal healthy blood donors. Disease activity in systemic lupus erythematosus correlated with higher exposure of Aleuria aurantia lectin-reactive fucosyl residues by immobilized IgG complexes. Top levels of Aleuria aurantia lectin-reactivity were found in samples taken during the highest activity of systemic lupus erythematosus. Our results show that native circulating IgG complexes from active systemic lupus erythematosus patients expose fucosyl residues and their glycan core is accessible to soluble lectins. Two putative mechanisms may contribute to the increased exposure of these glycans: (1) the canonical N-glycosylation site of the IgG-CH2 domain; (2) an IgG binding non-IgG molecule, like complement or C-reactive protein. In both cases the complexed IgG may be alternatively targeted to lectin receptors of effector cells, e.g. dendritic cells.